Correction: Self-Assembling Peptide Surfactants A6K and A6D Adopt a-Helical Structures Useful for Membrane Protein Stabilization. Membranes 2011, 1, 314-326 - Kamila Oglęcka; Charlotte A. E. Hauser; Furen Zhuang (Membranes, 2012)
We would like to request a correction to the author listing. The following changes should be made in respect to the original publication of this article [1]. [...]